ASSESSMENT SYSTEM FOR ARABIC LANGUAGE LEARNING WITHIN THE INDEPENDENT CURRICULUM - Pujiani, Ujiani (Kitaba, 2024)
The Arabic Language Learning Assessment System explores a range of evaluative approaches aimed at measuring student progress in Arabic language acquisition. This study delves into various assessment methods and strategies for evaluating communicative competencies, reading, writing, and other linguistic skills pertinent to Arabic. It also highlights the significance of adopting diverse and contextually appropriate assessment techniques. Moreover, the study discusses how an effective assessment framework can enhance students' comprehension and proficiency in Arabic. Findings indicate that the Independent Learning Curriculum significantly contributes to the educational process, with an emphasis on student engagement through both summative and formative assessments. It is recommended that educational institutions innovate by improving learning facilities, particularly through enhanced technological support, such as the integration of projectors in the learning environment. This study underscores the necessity for continuous development in educational tools and strategies to better support Arabic language learning.